Convergence of price dynamics assessed in view of Poland’s accession to the euro area focusing on deflation - Błaszczyk, Paweł; Fojutowski, Łukasz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
The primary aim of this study was to assess the degree of Poland’s convergence in terms of price stability, both at the stage of the country’s candidacy to the euro area and in relation to the euro convergence criteria (the so-called Maastricht criteria), and in the broader context of the ECB’s unified monetary policy. The time frame for this study covers the period of 2004– 2017. The starting point marks Poland’s accession to the EU, which is a pre-requisite for application to access the euro area. The closing time was chosen due to the availability of data, mainly from the Eurostat database. This was studied in view of the critical analysis of methodology and the method used to establish the Maastricht criterion for the dynamics of the general price level. The methodology of determining the inflation criterion is flawed and not matched to today’s economic conditions, including the definition of price stability applied in the practice of central banking, as well as in the context of the phenomenon of deflation commonly occurring in the last decade. As a consequence, the value of the criterion for a candidate country may turn out to be very low, and may unjustifiably increase the costs of accession to the euro area, also in the long-term perspective. Such a problem should be taken into account in the discussion on Poland’s accession to the euro area, which is usually of a political, as well as social and economic nature. This economic aspect, however, should be key in practice.